Impact of globalization on ukrainian retail trade - Юрко, Ігор Вікторович; Іржавська, Людмила Василівна (Technology audit and production reserves, 2014)
The impact of globalization on Ukrainian retail trade was determined. In recent years, trade has become not only an integral part of the economic structure, but also the way of impact on society. The retail sector acquires more and more important role − as the most important economic activity. Economic transformations, taking place in the country, in recent years has greatly changed the face of consumer market by increasing the number of producers, product saturation and enhancing the competition among sellers. In Ukraine, the process of globalization in retail trade has began in the late 1990s with the opening of the first supermarkets and hypermarkets now known as retail trade networks in the capital and cities with populations of over one million, and their subsequent distribution in major regional centers. The increase in real incomes and the ability of consumer buyers to get loans has become the main factors, promoting the development of network trade. In recent years, there has been a positive dynamic of growth in retail trade turnover, influenced either by global trends or specific features of Ukrainian retail development. Due to the presence of large retailers, the level of market concentration increases. A technical advantage of large retailers provides the cost efficiency. The results have shown that due to the presence of large retailers, the level of market concentration increases. The technical advantage of large retailers provides the cost efficiency.